Environmental Enrichment in Cancer as a Possible Tool to Combat Tumor Development: A Systematic Review - Fernandes, Matheus Santos de Sousa; Lacerda, Tiago Ramos; Fidélis, Débora Eduarda da Silva; Santos, Gabriela Carvalho Jurema; Filgueira, Tayrine Ordonio; de Souza, Raphael Fabrício; Lagranha, Claúdia Jacques; Lira, Fábio S. [UNESP]; Castoldi, Angela; Souto, Fabrício Oliveira (MDPI, 2023)
This systematic review aims to evaluate the influence of environmental enrichment (EE) on oncological factors in experimental studies involving various types of cancer models. A comprehensive search was conducted in three databases: PubMed (161 articles), Embase (335 articles), and Scopus (274 articles). Eligibility criteria were applied based on the PICOS strategy to minimize bias. Two independent researchers performed the searches, with a third participant resolving any discrepancies. The selected articles were analyzed, and data regarding sample characteristics and EE protocols were extracted. The outcomes focused solely on cancer and tumor-related parameters, including cancer type, description of the cancer model, angiogenesis, tumor occurrence, volume, weight, mice with tumors, and tumor inhibition rate. A total of 770 articles were identified across the three databases, with 12 studies meeting the inclusion criteria for this systematic review. The findings demonstrated that different EE protocols were effective in significantly reducing various aspects of tumor growth and development, such as angiogenesis, volume, weight, and the number of mice with tumors. Furthermore, EE enhanced the rate of tumor inhibition in mouse cancer models. This systematic review qualitatively demonstrates the impacts of EE protocols on multiple parameters associated with tumor growth and development, including angiogenesis, occurrence, volume, weight, and tumor incidence. Moreover, EE demonstrated the potential to increase the rate of tumor inhibition. These findings underscore the importance of EE as a valuable tool in the management of cancer.
Keywords: angiogenesis; cancer; enriched environment; pro-oncogenic factor; tumor growth